(3cJGH GdCeQGV hGdcaGQGJ hGdWH hGdQbjGJs - (3VjGA GdOjf GdebOSj , eMeO Hf YHO GdhGMO Hf CMeO Hf YHO GdQMef GdSYOj GdebOSj, VjGA GdOjf CHh YHO Gddg,J (B643 (3g` s ((3YKeGf Hf HdHGf Hf YHO Gddg GdebGJdi s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdGeGeR SdjeGf Hf MeRI bGd GdMeO ddg MeOkG jhGai fYeg s
(3BNQgG (B:s
(3cGf QShd Gddg Udi Gddg Ydjg hSde EPG ZRG Ch SGaQ aCOQcg Gddjd bGd jG GQVi QHi hQHc Gddg GdMOjK QhGg CHh OGhO GdfSGFi s
(3hQGhjI CHh GdaVd SdjeGf Hf MeRI Hf CMeO Hf YeQ GdebOSi HgG fXGe GdJYbjHIs
(3YdjgG SeGYGJ dYdgG efbhdI Yf GdCUd GdefJSN efg JGQjgG (B630 (3g` (B639(3g` (B704 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B263s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs